Reader reaction to "A robust method for estimating optimal treatment regimes" by Zhang et al. (2012). Issue 1 (16th September 2014) - Taylor, Jeremy M. G.; Cheng, Wenting; Foster, Jared C.
Summary A recent article (Zhang et al., 2012, Biometrics168, 1010–1018) compares regression based and inverse probability based methods of estimating an optimal treatment regime and shows for a small number of covariates that inverse probability weighted methods are more robust to model misspecification than regression methods. We demonstrate that using models that fit the data better reduces the concern about non‐robustness for the regression methods. We extend the simulation study of Zhang et al. (2012, Biometrics168, 1010–1018), also considering the situation of a larger number of covariates, and show that incorporating random forests into both regression and inverse probability weighted based methods improves their properties.